Global and Blow-up Solutions to a $p$-Laplace Equation with Nonlocal Source and Nonlocal Boundary Condition (Communications in Mathematical Research, 2021)
This paper deals with an evolution $p$-Laplace equation with nonlocalsource subject to weighted nonlocal Dirichlet boundary conditions. We give sufficientconditions for the existence of global and non-global solutions.